Integrating Local Culture into STEM-Based Learning in Asean Elementary Schools: A Literature Review - Nurhairani, N; Sugito, S; Suyanta, S; Haryanto, H (Proceedings International Conference on Education Innovation and Social Science, 2024)
This article examines the implementation of Science, Technology, Engineering, and Mathematics (STEM) learning in several ASEAN countries, such as Singapore, Malaysia, Indonesia, and Thailand. This article uses an integrative literature review method to explore how culture in Southeast Asia (ASEAN) countries contributes to STEM learning in primary schools. Data were analyzed from journals and research relevant to the theme. The literature review indicates that STEM implementation in ASEAN countries has significant differences, influenced by government policies, culture, and language. While some countries, such as Singapore, show substantial progress in integrating STEM into the curriculum, implementation at the primary school level still lags behind in most ASEAN regions. This article emphasizes the importance of cultural integration in STEM learning design to create more engaging, relevant, and meaningful learning experiences for students. This integration involves understanding the context, utilizing local cultural resources, and developing learning materials tailored to students' needs and interests. Developing a cultural analysis framework in STEM approaches for primary school is a crucial step to achieve this. The research concludes that culturally responsive STEM approaches can potentially increase students' motivation, engagement, and understanding of STEM concepts while preparing them for future global challenges. Cultural integration in STEM will create a more inclusive and relevant education system for all students while supporting participation and collaboration in building a broader perspective.